Mycobacterial infection in aquarium fish - P. Lescenko; L. Matlova; L. Dvorska; M. Bartos; O. Vavra; S. Navratil; L. Novotny; I. Pavlik (Veterinární Medicína, 2003)
In the first part of the study, 70 aquarium fish of different species, originating from stocks from the CzechRepublic, were pathomorphologically examined for the presence of granulomatous lesions. Granulomas were diagnosed in 44 (62.9%) fish. From these, acid fast rods (AFR) were found in 29 (65.9%) by staining according to Ziehl-Neelsen (Z-N). In the remaining 26 (37.1%) fish without granulomatous lesions, the presence of AFR was microscopically proven in 3 (11.5%) fish. In the second part of the study, direct microscopic examinations according to Z-N and culture examinations for the presence of mycobacteria were carried out in 17 randomly selected fish of the Apistogramma cacatuoides, Trichogaster leeri, Trichogaster trichopterus, Pterophyllum scalare, Paracheirodon axelrodi species with the pathomorphological discovery of granulomas. Mycobacteria were culturally found in 12 (70.6%) fish. Mycobacterium marinum, pathogenic for fish, was isolated from 6 fish, of which in one M. triviale was found at the same time and in two M. avium mixed serotypes 6, 8 and 9 (genotype IS901-, IS1245+). M. gordonae was isolated from a further 6 fish, of which in two M. avium mixed serotypes 6, 8 and 9 (genotype IS901-, IS1245+) was also isolated at the same time. A mixed infection of more species of mycobacteria was therefore found in five fish. In these it may be assumed that the mycobacteria of the M. triviale and M. avium mixed serotypes 6, 8 and 9 (genotype IS901-, IS1245+), non-pathogenic for fish, came from the water environment and "merely contaminated" the tissues of the fish.